Pendugaan laju sedimentasi pada kolam tanah budidaya ikan patin intensif di Desa Koto Mesjid Kecamatan XIII Koto Kampar - Saberina Hasibuan; Syafriadiman Syafriadiman; Atria Martina; Henni Syawal; Rinaldi Rinaldi (Riau Journal of Empowerment, 2019)
The potential of fisheries in Koto Mesjid village XIII Koto Kampar districts has had a tremendous impact on people's income. The total area of ​​the Patin pond in Koto Mesjid village has reached 62 hectares. The production reaches six tons per day. Training in prediction the rate of sedimentation in intensive catfish aquaculture ponds in the village of Koto Mesjid has resulted in a way to monitor the quality of pond water through the measurement of suspended solids using a solid trap device. The average suspended solids at all pond ages are 19.5 ml / L per day and 129.25 ml / L per week. Based on this data, the management of the pond bottom must be carried out every harvest, mainly when drying the pond needs to drain mud. Patin fish farmers have very high enthusiasm to practice the tools in their respective ponds. The existence of this counseling is very useful in providing knowledge so that people who work as Patin fish farmers can manage the time to replace pond water easily.